The Implied Power through the Use of Personal Pronouns in Obama’s Speeches: Critical Discourse Analysis - Dahnilsyah (Prodi Administrasi Pendidikan Program Pascasarjana Universitas Riau, 2017)
This is a qualitative study with descriptive data presentation. It is aimed at investigating the tendency of abuse of power in exploiting personal pronouns of Obama‘s political speeches.The employed grand theory in this study is social cognition theory introduced by Teun, A. Vandijk. There are three aspects that need to be empowered: textual, social cognition and social context in disclosing the implied meanings of the use of personal pronouns in Obama‘s political speeches. The data of this study were gathered by means of speech transcript collections of Obama‘s speeches: 2010, 2011 and 2014 concerning terrorism issues. These transcripts obtained from online media which had been spread worldwide. The objective of this study is to describe which personal pronouns frequently exploited by Obama in his political speeches and discover the hidden meanings of the adopted personal pronouns. The findings demonstrate that: (1) Obama, tends to use personal pronouns ‗we' and ‗our', (2) Obama seems to have been selective in exploiting personal pronouns by referring to both certain contexts and situations before and after the speech was delivered, (3) The features of Obama's speeches are rhetorical, persuasive and manipulative. In terms of cognition and social context, these speeches indicate that intelligence, personal and social experiences do influence towards the emergence of a discourse. The implicitly conditioned and engineered dominance and hegemony are not considered as a force or coercion. Rather, it is thought as a common and justified when being exposed frequently.